Platelet-Rich Plasma Increases Anti-inflammatory Markers in a Human Coculture Model for Osteoarthritis. (June 2015) - Osterman, Chelsea; McCarthy, Mary Beth R.; Cote, Mark P.; Beitzel, Knut; Bradley, James; Polkowski, Gregory; Mazzocca, Augustus D.
Background: Platelet-rich plasma (PRP) has anti-inflammatory effects with potential applications in the treatment of osteoarthritis (OA). Purpose: To use an in vitro coculture model of OA in human cartilage and synovium to investigate the anti-inflammatory effects of 2 different PRP preparations. Study Design: Controlled laboratory study. Methods: A coculture system was created using osteoarthritic cartilage and synovium from 9 patients undergoing total knee arthroplasty. Interleukin-1β (IL-1β) was added to each coculture to induce inflammation. Two PRP preparations were obtained—one yielding low white blood cell and platelet concentrations (PRPLP ) and one yielding high platelet and white blood cell concentrations (PRPHP ). Either PRPLP, PRPHP, or medium was added to the coculture wells. Control wells contained OA cartilage and synovium but neither IL-1β nor PRP. Normal, non-OA cartilage was obtained to establish baseline gene expression levels. Quantitative polymerase chain reaction was used to measure changes in markers of inflammation in the tissues (a disintegrin and metalloproteinase with thrombospondin motifs–5 [ADAMTS-5], tissue inhibitor of metalloproteinases–1 [TIMP-1], vascular endothelial growth factor [VEGF], aggrecan, and type I collagen) at 0, 24, 48, and 72 hours. Results: Treatment with PRPLP or PRPHP significantly decreased expression of TIMP-1 and ADAMTS-5 in cartilage, increased aggrecan expression in cartilage, and decreased ADAMTS-5, VEGF, and TIMP-1 expression in synovium compared with control cocultures ( P < .05). There was significantly less nitric oxide production in the PRPLP and PRPHP groups compared with controls ( P < .05). There were significant differences in gene expression in the normal cartilage compared with all 4 groups of OA cartilage at all 4 time points. Treatment with either PRPLP or PRPHP returned some gene expression to the same levels in normal cartilage but not for all markers of inflammation. Conclusion: This coculture model assessed 2 different PRP preparations and their anti-inflammatory effects over time on human OA cartilage and synovium. Both had a significant anti-inflammatory effect on gene expression; however, there was no difference in the anti-inflammatory effect between the 2 preparations. Clinical Relevance: Osteoarthritis is a leading cause of chronic disability, and less invasive treatment methods are needed. Study results suggest that PRP injections may be an effective alternative anti-inflammatory agent in the treatment of OA.